Il-6 and MSH3 in colorectal carcinoma: Expression, relationship, and prognostic significance in 171 colorectal carcinoma cases - Elif Kolay Bayram; Betul Ogut; Mehmet Arda Inan; Ayse Dursun (Indian Journal of Pathology and Microbiology)
Aims: Colorectal cancer (CRC), the most common type of gastrointestinal cancer, mostly develops as a result of environmental factors. Inflammation is a relatively uncommon but crucial contributor to its etiology, and inflammation is also thought to pose a risk in patients without a clinical diagnosis of inflammatory bowel disease. In cell lines, the proinflammatory cytokine interleukin-6 (IL-6) causes a cytosolic shift in the mismatch repair protein MSH3, accompanied by functional loss. This study aimed to evaluate IL-6 and MSH3 expression in 171 sporadic CRC samples by immunohistochemistry (IHC). High levels of IL-6 are hypothesized to cause MSH3 expression loss. We also explored the clinical/pathological aspects of IHC-detected MSH3 loss and the relationship between MSH3 expression and tumor-infiltrating lymphocytes (TILs). Materials and Methods: IL-6 and MSH3 IHC and H and E slides were evaluated by two pathologists. Clinical data were obtained from the institution’s database. Results: A relationship between MSH3 loss and IL-6 expression was not proven (P = 0.963). MSH3 staining was significantly reduced in the patient group with high TILs (P = 0.035). We observed 104 CRC cases (60.8%) with IL-6 expression and 85 cases (49.7%) with reduced MSH3 expression. Conclusion: This study did not demonstrate an association between IL-6 and MSH3 expression. As MSH3 is a relatively little-known protein, further large-scale studies are needed. The use of IHC to identify patients who may benefit from anti-IL-6 therapies in CRC in the future may be critical.